Exploration of the Modulatory Property Mechanism of ELeng Capsule in the Treatment of Endometriosis Using Transcriptomics Combined With Systems Network Pharmacology - Zheng, Weilin; Wang, Jie; Wu, Jiayi; Wang, Tao; Huang, Yangxue; Liang, Xuefang; Cao, Lixing (Frontiers in Pharmacology, 2021)
Endometriosis is a common gynecological disease and causes severe chronic pelvic pain and infertility. A growing evidence showed that Chinese medicine plays an active role in the treatment of endometriosis. ELeng Capsule (ELC) is a Chinese medicine formula used for the treatment of endometriosis for several years. However, the mechanisms of ELC have not been fully characterized. In this study, network pharmacology and mRNA transcriptome analysis were used to study various therapeutic targets in ELC. As a result, 40 compounds are identified and 75 targets overlapped with endometriosis related proteins. The mechanism of ELC for the treatment of endometriosis is based on the function modules of induce apoptosis, inhibit angiogenesis and regulate the immune mainly through the signaling molecules and interaction (neuroactive ligand-receptor interaction), immune system associated pathways (toll-like receptor signaling pathway), and the vascular endothelial growth factor (VEGF) signaling, MAPK signaling pathway based on network pharmacology. In addition, based on RNA-sequence analysis, we found that the mechanism of ELC were predominantly associated with the regulation the function modules of actin and cytoskeleton, epithelial-mesenchymal transition (EMT), focal adhesion, and immunity associated pathways. In conclusion, ELeng Capsule exerted beneficial effects on endometriosis, and the potential mechanism could be realized through functional modules, such as inducing apoptosis and regulating angiogenesis, cytoskeleton, and EMT. This work not only provides an insight of the therapeutic mechanism of TCM on treating endometriosis, but also may offer an efficient way for drug discovery and development from herbal medicine.